2014
DOI: 10.1155/2014/231948
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Surgical and Nonsurgical Treatment of Type II Odontoid Fractures in the Elderly

Abstract: Odontoid fractures type II according to Anderson and d'Alonzo are not uncommon in the elderly patients. Still, due to the paucity of evidence the published treatment guidelines are far from equivocal. This systematic review focuses on the published results of type II odontoid fracture treatment in the elderly with regard to survival, nonunion, and complications. After a systematic literature research 38 publications were included. A cumulative analysis of 1284 published cases found greater survival if elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 57 publications
(75 reference statements)
1
62
1
13
Order By: Relevance
“…Generally, it is important to note that many studies or reviews in the literature consist of rather small samples or small original study populations [8,26,30,31]. To the best of our knowledge, this series represents the largest study investigating mortality in patients aged 70 years and older with type II odontoid fractures treated with TAFOF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is important to note that many studies or reviews in the literature consist of rather small samples or small original study populations [8,26,30,31]. To the best of our knowledge, this series represents the largest study investigating mortality in patients aged 70 years and older with type II odontoid fractures treated with TAFOF.…”
Section: Discussionmentioning
confidence: 99%
“…However, controversies exist regarding the ideal treatment strategy for elderly patients, particularly those with verified atlanto-odontoid osteoarthritis (AO) [4,5]. For this patient population, conservative therapy strategies are associated with an increased mortality, a high non-union rate, and inferior quality of life [6][7][8][9]. Also, unacceptable complication rates are reported after halo fixator treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that these studies were simply underpowered to detect the mortality difference, and a meta-analysis including these studies did demonstrate a significant survival advantage associated with surgery. 39 The true reduction in mortality that can be attributed to surgery will probably remain unknown until a randomized-controlled trial on the topic can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical treatment with a cervical collar or halo vest has a nonunion rate of as high as 40%. 31 For this reason, surgical treatment is especially indicated in patients who have a higher risk for nonunion. In this context, surgical treatment with AOSF or posterior cervical instrumented fusion (PCIF) increases the fusion rate to more than 80% in many patient series.…”
Section: Surgical Indications For Type II Odontoid Fracturesmentioning
confidence: 99%
“…In this context, surgical treatment with AOSF or posterior cervical instrumented fusion (PCIF) increases the fusion rate to more than 80% in many patient series. 1,31 Some authors have reported up to 100% healing with posterior C1-2 arthrodesis with PCIF.…”
Section: Surgical Indications For Type II Odontoid Fracturesmentioning
confidence: 99%